Selling Cross-Border in Online Markets: The Impact of the Ban on Geoblocking Strategies - Marc Bourreau; Fabio M. Manenti (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We develop a model of strategic geoblocking, where two competing multi-channel retailers, located in different countries, can decide to block access to their online store from foreign consumers. We characterize the equilibrium when firms decide unilaterally whether to introduce geoblocking restrictions. We show that geoblocking results in a “puppy dog” strategy (Fudenberg and Tirole, 1984) for firms, which allows them to soften competition, but that it comes at the cost of lower demand. In the short term, a ban on geoblocking leads to lower prices, both offline and online. However, in the longer term, when firms can invest in increasing the demand from online shoppers, the ban may have adverse effects on investment and social welfare. We extend our analysis to account for price discrimination and investigate the role of shipping costs.
Keywords: L13; L41; L81; 330; cross-border sales; geoblocking; e-commerce; investment